Genome-wide association study for calving traits in Holstein-Friesian dairy cattle - BRADLEY, DANIEL (My University, 2014)
The enteropathogen Campylobacter jejuni is a major worldwide health and economic burden, being one of the leading causes of bacterial gastroenteritis and commonly linked to postinfectious onset of autoimmune disease. Chickens are a major vector for human infection and even though variation in avian colonization level is heritable, no previous studies have identified regions of the genome associated with colonization resistance. We performed a genome-wide association study of resistance to C. jejuni colonization in the avian intestine by controlling for population structure, which revealed a risk locus with genome-wide significance spanning the T-cadherin (CDH13) gene. A second possible risk locus was also identified close to calmodulin (CALM1), a calcium-activated modulator of cadherin function. In addition, gene expression analysis of mRNA sequencing profiles revealed that the relative expression of the two genes is significantly associated with colonization resistance. Functional studies have previously demonstrated involvement of cadherins and calmodulin in C. jejuni intracellular invasion and colonization of human intestinal epithelial cells in vitro. Consistent with this finding, our analysis reveals that variation surrounding these genes is associated with avian colonization resistance in vivo and highlights their potential as possible targets for control of the bacterium in avian and human populations.
PUBLISHED
Keywords: immunity; calmodulin; cadherin; epithelial cell invasion; intestinal homeostasis; GWAS